PENERAPAN ALGORITMA EDGE DETECTION DAN CLUSTERING MENGIDENTIFIKASI PENGENALANWAJAH DALAM E-ABSENSI - Rahmadani, Desy; Apdillah, Dicky (Smart Education, 2025)
Abstract: Absence is usually used to see the level of employee discipline. The discipline of each employee is usually assessed as an indicator to determine whether the employee is allowed to apply for a salary increase and so on. To be able to monitor the presence of employee attendance activities, an attendance system is needed that can record employee attendance and absence. Over time, the attendance system has developed. Various types of attendance systems have also developed, such as using barcode and fingerprint methods. Problems with the barcode attendance system arise when employee members do not carry cards or other tools that have been given barcodes, then employees will not be able to take attendance, while the shortcomings of the fingerprint method when someone's fingerprints are injured or dirty will interfere with the scanning process on the sensor. Employees are required to take attendance every working day. The purpose of attendance in an agency, especially to see the performance of the employee, will also improve the quality of the agency itself. In this study, only the edge detection and clustering algorithms were used with the data inputted into this system being photo image data. In testing using edge detection, it produces percentage values such as in the first test, the percentage level of photo similarity is 47.32%, in the second photo test, the percentage level of photo similarity is 57.27%, in the third photo test, the percentage level of photo similarity is 57.75%, in the third photo test, the percentage level of photo similarity is 77.14%. Keywords: Edge Detection Algorithm, Clustering, Identifying Face Recognition, E-Attendance, Web Abstrak: Absensi biasanya digunakan untuk melihat tingkat kedisipinan pekerja. Kedisipinan masing-masing pegawai atau karyawan biasanya dinilai sebagai indikator untuk menentukan apakah karyawan tersebut boleh untuk mengajukan kenaikan gaji dan lain sebagianya. Untuk dapat memantau adanya aktivitas kehadiran pegawai atau karyawan maka diperlukan sebuah sistem absensi yang dapat mencatat absensi kehadiran dan ketidakhadiran karyawan.Seiring berjalannya waktu sistem absensi kian berkembang. Berbagai jenis sistem absensi pula telah berkembang seperti dengan menggunakan metode barcode dan sidik jari. Permasalahan pada sistem absensi barcode muncul ketika anggota karyawan tidak membawa kartu yang atau alat lainnya yang telah diberi barcode, maka karyawan tidak akan bisa melakukan absensi sedangkan kekurangan dalam metode sidik jari ketika sidak jari seseorang terluka atau kotor akan menggangu proses scanning pada sensor. Pegawai atau karyawan diharuskan untuk melakukan absen setiap hari kerja. Tujuan absensi di instansi khususnya untuk melihat kinerja pegawai atau karyawan tersebut yang akan meningkatkan juga mutu dari instansi itu sendiri. Dalam penelitian ini hanya menggunakan algoritma edge detection dan clustering dengan data yang diinputkan dalam sistem ini ialah data citra foto. Dalam pengujian menggunakan edge detection menghasilkan nilai persentase seperti pada uji pertama terlihat tingkat persentase kemiripan foto ialah 47,32%, pada uji foto ke dua terlihat tingkat persentase kemiripan foto ialah 57,27%, pada uji foto ke tiga terlihat tingkat persentase kemiripan foto ialah 57,75%, pada uji foto ke tiga terlihat tingkat persentase kemiripan foto ialah 77,14%. Kata Kunci : Algoritma Edge Detection, Clustering, Mengidentifikasi Pengenalan Wajah, E-Absensi, Web